Effects of seed burial on germination, protein mobilisation and seedling survival in Dodonaea viscosa. (22nd October 2013) - Benítez‐Rodríguez, L.; Gamboa‐deBuen, A.; Sánchez‐Coronado, M. E.; Alvarado‐López, S.; Soriano, D.; Méndez, I.; Vázquez‐Santana, S.; Carabias‐Lillo, J.; Mendoza, A.; Orozco‐Segovia, A.; Arroyo, J.
Abstract Ecological restoration of disturbed areas requires substantial knowledge of the germination of native plants and the creation of novel methods to increase seedling establishment in the field. We studied the effects of soil matrix priming on the germination of Dodonaea viscosa seeds, which exhibit physical dormancy. To this end, we buried both pre‐scarified (in H2SO4, 3 min) and non‐pre‐scarified seeds in the Parque Ecológico de la Ciudad de México. After seeds were unearthed, they were post‐scarified for 0, 2, 6 and 10 min and their germination percentages compared to the germination of a control batch of laboratory‐stored seeds. For both control and unearthed seeds, the protein pattern was determined in the enriched storage protein fraction in SDS‐PAGE gels stained with Coomassie blue. Percentage germination increased as the scarification time increased. Pre‐scarification significantly increased percentage germination of post‐scarified seeds in relation to the control and non‐pre‐scarified seeds. In seeds unearthed from the forest site, the buried pre‐scarified seeds had relatively high percentage germination, even in the absence of post‐scarification treatment. A 48‐kDa protein was not found in unearthed, pre‐scarified seeds nor in the control germinated seeds, indicating that mobilisation of this protein occurred during soil priming. Burying seeds for a short period, including the beginning of the rainy season, promoted natural priming, which increased protein mobilisation. Functionally, priming effects were reflected in high percentage seedling survival in both the shade house and the field. Seed burial also reduced the requirement for acidic post‐scarification.